Sorting out the Stars: The First Publication of 'Delia' and Its Attribution to Burns. Issue 1 (March 2022) - Baraniuk, Carol; Leask, Nigel; Scott, Patrick
Abstract : This essay discusses the disputed authorship of the short poem 'Delia'; locates for the first time the correct London newspaper in which the poem was first printed, as written by Burns, before its appearance in Belfast; confirms earlier research and speculation by Lucyle Werkmeister and further elucidates the relationship of Burns with the editor Peter Stuart, and with Stuart's 'spurious' Star newspaper; identifies, also for the first time, a previous publication of the poem with music in The Feast of Apollo (London, ?1787); and concludes that 'Delia' (and the letter that accompanied it in newspaper publication) is very unlikely to be by Burns.